EXPLORING THE UTILIZATION OF GOVERNMENT SOCIAL MEDIA AS AN INFORMATION SOURCE - Ernungtyas, Niken Febrina; Irwansyah, Irwansyah; Boer, Rino F; Qadrifa, Sabrina Sofi (Jurnal Studi Komunikasi dan Media, 2024)
Developments in digital transformation and information technology have led to the transformation of society into an information society. The government needs to leverage government social media, which utilizes information and communication technologies (ICT), to disseminate effective, affordable, and up-to-date public information to the public. As a result, the purpose of this research is to explore the use of government social media as an information source. A survey of 263 respondents was collected through questionnaires. The research analysis employed in this study was descriptive statistics. The findings illustrate that Instagram is the most frequently used social media platform by citizens to search for public information. It was found that in the last four years, the number of new followers on the government's Instagram, Twitter, Facebook, and YouTube accounts has increased, with most of the new followers coming in the last 1-2 years. Most respondents who follow the government's Instagram and Twitter mentioned general information and education/scholarship information as their reasons for following. The government's Facebook followers mostly chose general and health/pandemic information. Meanwhile, government YouTube followers do so for education/scholarship information and health/pandemic information.